Examining the Implementation of School-Wide Positive Discipline Intervention and Its Impact on Teacher Beliefs, Values and Practices - Collins, Isreal J. (2007)
The frequent occurrence of negative student behaviors such as bulling, verbal abuse, and disrespect remain a key concern for teacher. Teachers report instances of simple disrespect, noncompliance, poor peer interactions, cursing, making fun of one another, grabbing, pushing and being of-task as common occurrences in their classrooms. Teachers are expected and required to manage student behavior through the implementation of a well designed classroom management plan. Student disruptions through negative behavior require constant alteration of their management plan, reducing instructional time, and leaving teachers with high levels of personal frustration and stress. School districts around the country have begun to look for different strategies to address challenging behaviors by students that disrupt the daily routines in their schools. School-wide Positive Behavior Support is a strategy that is currently being implemented in more than 2900 schools in 34 states. This approach has gained popularity in schools for several reasons including its effectiveness in reducing school-wide discipline problems, the publics increased concerns regarding school violence, and the requirement of the Individuals with Disabilities Education Improvement Act for the use of positive behavioral supports to address challenging behaviors. 2 Since PBS is a form of value-based systemic change, teachers who participate are required to reexamine and possibly change their beliefs, philosophies and values about disciplinary practices. The purpose of this study was to examine the implementation of school-wide positive discipline intervention and its impact on teacher beliefs, values and practices that resulted in a changed school climate at a Middle School in Northeast Georgia. As a quantitative method, a survey instrument was used to assess the changes in teacher beliefs, values and practices toward discipline. The survey was administered by the researcher during a regular weekly scheduled faculty meeting. Descriptive statistics reported the mean and standard deviation